Three manual noncommercial methods to prepare equine platelet-rich plasma - Segabinazzi, Lorenzo G. T. M.; Podico, Giorgia [UNESP]; Rosser, Michael F.; Nanjappa, Som G.; Alvarenga, Marco A.; Canisso, Igor F. [UNESP] (MDPI, 2021)
In light of PRP’s increasing popularity in veterinary practice, this study aimed to compare three manual methods to prepare and cool equine PRP. The blood of 18 clinically healthy mares was collected via venipuncture in a blood transfusion bag (method 1), blood tubes (method 2), and a syringe (method 3). In method 1, samples were double centrifuged; method 2 involved one centrifugation, and in method 3 the syringe was kept in an upright position to sediment for 4 h. After processing with three methods, PRP and platelet-poor plasma (PPP) were extracted and assessed for red (RBC) and white blood cell counts (WBC), platelet counts, and viability. In a subset of mares (n = 6), samples were processed with the three methods, and PRP was evaluated at 6 and 24 h postcooling at 5◦C. Method 1 resulted in the highest and method 3 in the lowest platelet concentration (p < 0.05), and the latter also had greater contamination with WBC than the others (p < 0.001). Platelet viability was similar across treatments (p > 0.05). Cooling for 24 h did not affect platelet counts in all methods (p > 0.05); however, platelet viability was reduced after cooling PRP produced by method 3 (p = 0.04), and agglutination increased over time in all methods (p < 0.001). The three methods increased (1.8–5.6-fold) platelet concentration in PRP compared to whole blood without compromising platelet viability. In conclusion, all three methods concentrated platelets and while cooling affected their viability. It remains unknown whether the different methods and cooling would affect PRP’s clinical efficacy.
Keywords: Blood byproduct; Endometritis; Horse; Platelet concentrate; Platelet viability